Healthy Living for Elders: Use Your Medicines Safely! - Paulina Wittkowsky; Linda B. Bobroff; Emily Minton (EDIS)
Revised! FCS8594, a 2-page illustrated fact sheet by Paulina Wittkowsky, Linda B. Bobroff, and Emily Minton, provides tips for elders to use medicines safely. Published by the UF Department of Family Youth and Community Sciences, December 2009.